PENGARUH CAPITAL INTENSITY, INTENSITAS ASET TETAP DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE : PENGARUH CAPITAL INTENSITY, INTENSITAS ASET TETAP DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE - Caru Gaur, Maria Gracella; Wulandari, Ika (ITB AAS Indonesia Surakarta, 2025)
Tax revenue is crucial for a country as it constitutes one of the largest sources of state revenue. However, tax avoidance is also a significant issue for the country due to the high rate of tax evasion, particularly by companies. Therefore, this study aims to examine and analyze how capital intensity, fixed asset intensity, and financial distress influence tax avoidance, particularly in manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The research methodology used is quantitative and utilizes secondary data obtained from the companies' financial statements. Purposive sampling was used to select 201 samples that met the criteria. The analysis technique used Multiple Linear Regression, tested in SPSS version 23. The findings of this study indicate that capital intensity has a positive effect on tax avoidance, while fixed asset intensity and financial distress have a negative effect on tax avoidance. This study provides implications for companies to be more prudent in the investment strategy and management of fixed assets, as well as to maintain financial stability to avoid risky tax decisions. For the government, the findings serve as input to strengthen regulations, supervision, and a risk-based audit system to minimize the practice of tax avoidance, while future researchers are encouraged to expand the study by incorporating additional variables to obtain more comprehensive results